2021
DOI: 10.3389/fcimb.2020.612931
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides and Cell-Penetrating Peptides for Treating Intracellular Bacterial Infections

Abstract: Bacterial infections caused by intracellular pathogens are difficult to control. Conventional antibiotic therapies are often ineffective, as high doses are needed to increase the number of antibiotics that will cross the host cell membrane to act on the intracellular bacterium. Moreover, higher doses of antibiotics may lead to elevated severe toxic effects against host cells. In this context, antimicrobial peptides (AMPs) and cell-penetrating peptides (CPPs) have shown great potential to treat such infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 61 publications
0
53
0
Order By: Relevance
“…In accordance with the strategy presented in Figure 1, we developed hybrid peptides that contained a cell penetrating peptide (CPP) (fragment of Tat-peptide [60]) at the N-termini and an amyloidogenic sequence at the C-termini, which was predicted using bioinformatics tools [51]. The two sites were linked by four glycines.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the strategy presented in Figure 1, we developed hybrid peptides that contained a cell penetrating peptide (CPP) (fragment of Tat-peptide [60]) at the N-termini and an amyloidogenic sequence at the C-termini, which was predicted using bioinformatics tools [51]. The two sites were linked by four glycines.…”
Section: Introductionmentioning
confidence: 99%
“…AMPs and CPPs are very similar in structure, sequence, and membrane activity [ 63 ]. Moreover, some studies have evaluated the antimicrobial activity of CPPs and showed that AMPs could also reach the cytoplasmic target through nonmembrane permeability [ 40 , 65 , 66 ]. CPPs mainly focus on mammalian cells and are used as cell delivery tools for drugs and biomolecules [ 67 , 68 ].…”
Section: Antimicrobial Mechanism Of Ampsmentioning
confidence: 99%
“…The AMPs, also known as host defense peptides (HDPs) are commonly found in multicellular eukaryotes, usually expressed constitutively [21] and, like the complement system, are evolutionarily ancient components. In comparison to antibiotics, AMPs may be considered "natural antibiotics" expressed across the phylogenetic kingdoms [22] and causing pathogen cell disruption through non-specific interactions with their membrane surface [23].…”
Section: Renewing Antimicrobial Peptides Potentialmentioning
confidence: 99%
“…In this context, AMPs can be used as rediscovered [37] immunological effectors, to damage specific bacteria and target lysis of the pathogenic surface. Recent reports include among advantages the lesser tendency [38] to generate resistance [39], a low propensity to develop toxicity [25], better control of infection by intracellular bacterial pathogens as opposed to antibiotic ineffectiveness [21], anti-biofilm effects [25,35,40], and activation of immune cells [41]. Interestingly the patterns of mobile genetic elements are entirely different between the antibiotic and antimicrobial peptide resistance genes [42].…”
Section: Renewing Antimicrobial Peptides Potentialmentioning
confidence: 99%